PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN MATEMATIKA PADA SISWA MIN 16 BENER MERIAH - Sinema Rejeki Sinema Rejeki (Lembaga Sepercenter, 2025)
This classroom action research (CAR) aims to improve mathematics learning outcomes through the application of the Contextual Teaching and Learning (CTL) model to students at MIN 16 Bener Meriah. The background to this research is the low learning outcomes of students caused by mathematics learning that is still teacher-centred and does not relate the material to the real lives of students. This study used the Kemmis and McTaggart ACT model, which was implemented in two cycles, each consisting of the stages of planning, implementation of actions, observation, and reflection. The research subjects were students in class ... at MIN 16 Bener Meriah. Data collection techniques included learning outcome tests, observation, and documentation. The results showed that the application of the CTL model could improve students' mathematics learning outcomes, both in terms of average scores and learning completion rates. Thus, the CTL learning model is effective for use in mathematics learning at MIN 16 Bener Meriah.